Decentralised priority-based shortest job first queue model for IoT gateways in fog computing. (20th August 2022) - Jayashree, N.; Babu, B. Sathish; Talwar, Basavaraj
An increased growth in time-critical IoT applications, led to a rise in real-time resource requirements. The stringent deadlines on latency have made IoT applications move out from far away cloud servers to distributed fog computing devices infrastructure which is available locally. To meet the touchstones of deadlines and processing times, there is a need to prioritise the job scheduling through the IoT gateways to appropriate fog devices. Studies showed that the queuing models exhibit uncertainties in choosing suitable computing devices, applying priorities to the jobs, deadline achievements, and minimum latency constraints. In this paper, we propose a Decentralised Priority-based Shortest Job First (DPSJF) queuing model for the IoT gateways for a fog computing infrastructure, which uses the priority-based jobs sorting technique to achieve better performance and also overcome most of the uncertainties in queuing.